Pengaruh Penggunaan Model Pembelajaran Kooperatif Tipe Scramble Berbantuan Media Powerpoint terhadap Hasil Belajar Tematik Peserta Didik Kelas VB di SDN 36 Pontianak Selatan - Dian Pratiwi; Hairida Hairida; Rio Pranata (Departement of Mathematics Education, 2024)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble morals, and the skills needed by themselves, society, nation and state. Efforts that can influence student learning outcomes are that a teacher can or uses various learning methods or models that can create an interesting and enjoyable learning atmosphere and environment. However, in reality on the ground, teachers are less optional in using media and learning models. Teachers often apply lecture, question and answer and discussion methods which are usually called conventional learning models, and teachers in the learning process only use books and students only listen to the teacher's explanations, take notes and repeat lessons at home and memorize when there are tests. Teachers dominate too much in the learning process and students are given less space to talk, express opinions, ask questions and express opinions. The type of research used is experimental research. The approach used is a quantitative method approach. The research design used is Quasi Experimental Design or pseudo-experiment. The form of this research design is a Nonequivalent Control Group Design. The population and sample in this research was determined to be all class V students at SDN 36 South Pontianak for the 2023/2024 academic year, totaling 58 students. This research data collection method uses tests, observation, documentation and interviews. The data collection instruments for this research are test questions and documentation. The data analysis technique for this research uses descriptive statistical analysis, inferential statistical analysis. Based on the research, research data was obtained which showed that the average pretest score for the experimental class was 56.55 and the average post-test score for the experimental class was 80.34.